A new multiplex PCR for the accurate identification and differentiation of Salmonella enterica serovar Gallinarum biovars Pullorum and Gallinarum - Xiong, Dan; Yuan, Li; Song, Li; Jiao, Xinan; Pan, Zhiming (Frontiers in Microbiology, 2022)
Salmonella enterica serovar Gallinarum biovars Pullorum and Gallinarum represent the most common causative agents of chicken salmonellosis, a disease associated with high mortality and morbidity among chickens worldwide. Traditional methods to identify Salmonella have relied on biochemical reactions and serotyping. However, the conventional methods are complicated, time-consuming, laborious, and expensive. Furthermore, it is challenging to differentiate between S. Pullorum and S. Gallinarum via biochemical assays and serotyping because of their antigenic similarity. Although a number of PCR-based protocols have been developed, a PCR method for the identification and discrimination of S. Pullorum and S. Gallinarum simultaneously is lacking. Herein, we developed a one-step multiplex PCR method for the accurate detection and discrimination of S. Pullorum and S. Gallinarum. This multiplex PCR assay is based on three genes, with the I137_14445 and ybgL genes being key targets for the specific identification and differentiation of S. Pullorum and S. Gallinarum, and stn being included as a reference gene for the Salmonella genus. In silico analysis showed that the I137_14445 gene is present in all Salmonella serovars, except for S. Gallinarum, and could therefore be used for the identification of S. Gallinarum. A 68-bp region of difference in ybgL was found to be deleted only in S. Pullorum after comparison with S. Gallinarum and other Salmonella serovars, and this could therefore be used for the specific identification of S. Pullorum. The developed PCR assay was able to distinguish S. Pullorum and S. Gallinarum from 75 different Salmonella strains and 43 different non-Salmonella pathogens with excellent specificity. The minimum detection limit of genomic DNA of S. Pullorum and S. Gallinarum was 21.4 pg/μL, and the minimum number of detectable cells was 100 CFU. This PCR assay was also applied to analyze Salmonella isolates from a chicken farm. The PCR assay successfully discriminated S. Pullorum and S. Gallinarum from other Salmonella serovars, and the results were in agreement with the results of the traditional serotyping assay. Our newly developed multiplex PCR assay represents a potent, simple, and cost-effective tool for the specific and sensitive identification and differentiation of S. Pullorum and S. Gallinarum.